Diagnostic performance of GcfDNA in kidney allograft rejection: a meta-analysis - Yang, Hongji; Wang, Duo; Sun, Xin; Wang, Hailian; Lan, Yang; Wei, Liang (Frontiers in Physiology, 2024)
In this comprehensive meta-analysis, our objective was to evaluate the diagnostic utility of graft-derived cell-free DNA (GcfDNA) in kidney allograft rejection and explore associated factors. We conducted a thorough search of PubMed, Embase, and the Cochrane Library databases, spanning from their inception to September 2022. Statistical analysis was executed utilizing Stata 15, Meta-DiSc 1.4, and Review Manager 5.4 software. The combined pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and the area under the summary receiver operating characteristics (SROC) curve from the synthesis of findings across ten studies were as follows: 0.75 (0.67 -0.81), 0.78 (0.72 -0.83), 3.36 (2.89-4.35), 0.32 (0.24 -0.44), 8.77 (4.34-17.74), and 0.83 (0.80-0.86), respectively. Among the ten studies primarily focused on GcfDNA's diagnostic potential for antibody-mediated rejection (ABMR), the optimal cut-off threshold demonstrated substantial diagnostic efficacy, with pooled sensitivity, specificity, PLR, NLR, DOR, and area under the SROC curve values of 0.83 (0.74-0.89), 0.75 (0.70-0.80), 3.37 (2.64-4.30), 0.23 (0.15-0.36), 14.65 (7.94-27.03), and 0.85 (0.82-0.88), respectively. These results underscore the high diagnostic accuracy of GcfDNA in detecting rejection. Furthermore, the optimal cut-off threshold proves effective in diagnosing ABMR, while a 1% threshold remains a robust diagnostic criterion for rejection. Notably, for ABMR diagnosis, droplet digital PCR (ddPCR) emerges as a superior method in terms of accuracy when compared to other techniques. Nonetheless, further research is warranted to substantiate these findings.We not only examined the precision of GcfDNA in diagnosing rejection reactions but also scrutinized the factors influencing its accuracy.The research outcomes will furnish invaluable insights for the clinical implementation of GcfDNA.However, it's worth noting that the overall sample size included in this study was relatively small, which imposes constraints on the interpretability of the results.